Optimalisasi Pendapatan Daerah di Era Otonomi dan Munculnya Perda-perda Bermasalah - Maria Rosarie Harni Triastuti (Jurnal Administrasi Publik, 2008)
Autonomy and fiscal decentralization have an impact to local governments in creating and improving their autonomy to increase their revenue. In many cases, many regional by-laws connected with local tax and local retribution have potential proble to the investment in local territories. Hundreds of regional by-laws have trouble in any way. To deal with this problem, the central government makes a new rule of fiscal autonomy to optimize local revenue. Autonomy doesn't mean being free to do, tho think and to make a rule, but how to increase local capacity without making any problems to their district.Keywords: fiscal autonomy, problematic regional by-laws, new rule of policy